Використання нанорідин для підвищення ефективності огрудкування залізовмісної шихти - Петренко, В.О.; Комиш, Д.В.; Бойко, М.М.; Ковальов, Д.Ю.; Верещак, Д.В. (Physico-technological Institute of Metals and Alloys, 2025)
The article investigates the possibility of improving the efficiency of iron-containing charge agglomeration by using nanofluids based on colloidal solutions of clay minerals. The selection of an agglomeration activator composed of attapulgite and montmorillonite is substantiated, given their high specific surface area, hydrophilicity, ion exchange capacity, and naturalnanoscale structure, which enhance the agglomeration properties of the charge. A stable nanofluid was obtained throughultrasonic dispersion and applied in laboratory experiments to simulate the agglomeration process. Laboratory studies demonstrated that the introduction of nanofluid significantly increases the yield of the target agglomerationfraction (3–7 mm), especially at an optimal moisture content of approximately 12 %. However, further moisture increase to 13–13.5 % led to over-wetting, which negatively affected the strength of the granules and caused particle agglomeration. Industrial-scale pilot tests were conducted at sintering machine No. 6 of the agglomeration shop of ArcelorMittal Kryvyi Rih using three different grades of agglomeration activator produced by the company "KOSH." A dosing and injection system was designed for feeding the nanofluid into the mixing drum. Despite the positive effect observed in laboratory conditions, the pilot-scale trials did not show a significant increase in the productivity of the sintering machine. It was determined that themain limiting factor is the imperfect design of the mixing drum, which fails to create optimal conditions for efficient granuleformation. The obtained results confirm the potential of using nano-dispersed clay-based additives in the agglomeration process. However, they also highlight the need for technical modernization of the equipment in order to fully realize the benefits of these innovative process enhancements.